2020
DOI: 10.1111/maps.13461
|View full text |Cite
|
Sign up to set email alerts
|

Visible–near infrared spectral indices for mapping mineralogy and chemistry with OSIRISREx

Abstract: The primary objective of the Origins, Spectral Interpretation, Resource Identification, and Security-Regolith Explorer (OSIRIS-REx) mission is to return to Earth a pristine sample of carbonaceous material from the primitive asteroid (101955) Bennu. To support compositional mapping of Bennu as part of sample site selection and characterization, we tested 95 spectral indices on visible to near infrared laboratory reflectance data from minerals and carbonaceous meteorites. Our aim was to determine which indices r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 99 publications
(105 reference statements)
1
8
0
Order By: Relevance
“…In fact, OVIRS probes the uppermost surface of Bennu, where scattering properties are sensitive to very small particles comparable in size to that of the incoming light, while OTES is sensitive to larger particles and sounds the first subsurface. Hamilton et al (2020) showed that a ∼ 5 µm-thick coating of dust, with dominantly particles size in the 5-50 µm range, result in a very small change in total emissivity spectral contrast. The presence of dust blanketing the surface of Bennu was also suggested from the analysis of DellaGiustina et al (2019), who first reported the spectral phase reddening evident in OCAMS data.…”
Section: Comparison With Other Low-albedo Bodiesmentioning
confidence: 99%
“…In fact, OVIRS probes the uppermost surface of Bennu, where scattering properties are sensitive to very small particles comparable in size to that of the incoming light, while OTES is sensitive to larger particles and sounds the first subsurface. Hamilton et al (2020) showed that a ∼ 5 µm-thick coating of dust, with dominantly particles size in the 5-50 µm range, result in a very small change in total emissivity spectral contrast. The presence of dust blanketing the surface of Bennu was also suggested from the analysis of DellaGiustina et al (2019), who first reported the spectral phase reddening evident in OCAMS data.…”
Section: Comparison With Other Low-albedo Bodiesmentioning
confidence: 99%
“…Based on early OSIRIS-REx mission data (Hamilton et al 2019), Bennu is still most similar to CM2s, now more specifically Cold Bokkeveld (CM2.2 in the classification of Rubin et al 2007), other CM2.2 and CM2.1 chondrites, and CM1/2 chondrites, although not an exact match to any one as-recovered meteorite. As new meteorite spectra are acquired and added to spectral libraries (Takir et al 2013;McAdam et al 2015;Garenne et al 2016;Kaplan and Milliken 2016;Beck et al 2018;Lantz et al 2018;Bates et al 2020;Kaplan et al 2020), additional good matches may be recognized, enabling refined interpretation.…”
Section: Sample Return Mission Target Asteroids and Corresponding Meteorite Groupsmentioning
confidence: 99%
“…Early OSIRIS-REx OVIRS and OTES whole-diskintegrated spectra are spatially uniform across Bennu's surface at the spatial resolutions of tens to hundreds of meters reported to date; acquisition, reduction, and interpretation of spatially resolved data are ongoing (Hamilton et al 2019;Kaplan et al 2020). A strong absorption feature at~2.7 μm in OVIRS spectra is ubiquitous on Bennu's surface (Hamilton et al 2019;Kaplan et al 2020).…”
Section: Surface Materials As Inferred From Early Mission Datamentioning
confidence: 99%
See 2 more Smart Citations